2017
DOI: 10.1001/jamaoto.2017.1621
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Important Difference in Voice Handicap Index–10

Abstract: These findings suggest that a difference of 6 on the VHI-10 may represent an MID. This difference was associated with a moderate change on the global rating scale, and the small-change and no-change categories were indistinguishable. Given the lack of differentiation between small and no change and the modest correlation between the global change score and change in the VHI-10 score, additional studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 35 publications
1
62
1
Order By: Relevance
“…In patients with vocal fold paralysis, an improvement of 4 points on the VHI‐10 scale has been suggested to be the minimal clinically important difference that results in a perceivable voice change . Misono et al also reported on patients with a variety of vocal fold disorders and found that the minimal important difference on the VHI‐10 scale was 6 points . Currently, these are the only reference values to indicate a clinically significant voice improvement that is notable by patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with vocal fold paralysis, an improvement of 4 points on the VHI‐10 scale has been suggested to be the minimal clinically important difference that results in a perceivable voice change . Misono et al also reported on patients with a variety of vocal fold disorders and found that the minimal important difference on the VHI‐10 scale was 6 points . Currently, these are the only reference values to indicate a clinically significant voice improvement that is notable by patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 Misono et al also reported on patients with a variety of vocal fold disorders and found that the minimal important difference on the VHI-10 scale was 6 points. 17 Currently, these are the only reference values to indicate a clinically significant voice improvement that is notable by patients. In the fat-injection group, only half of the patients who were improved at their final visit did so by at least 4 points on the VHI-10 scale.…”
Section: Discussionmentioning
confidence: 99%
“…The test-retest reliability was excellent for patients and good for controls indicating a reliable questionnaire, suitable for longitudinal studies. The patient group and the control group had changes in scores of 1.0 ± 3.0 and -0.4 ± 1.5 points respectively in the test-retest interval which is well below the estimated minimal important measurement difference of six points of the original VHI-10 score [15]. Misono et al described limitations of the original VHI-10's ability to distinguish between no change and a small change in the perception of the severity of the voice disorders, and indicated that the questionnaire might not be suitable for evaluating small differences after treatment [15].…”
Section: Discussionmentioning
confidence: 69%
“…The VHI-10 has shown a good correlation to the results of the VHI-30 and has been thoroughly validated by internal consistency, reliability, and test-retest reliability tests [12,13]. In addition, normative values [14] and minimal important differences [15] has been established for the questionnaire and it now exists in multiple languages [16][17][18]. Thus, the VHI-10 is a well-suited clinical tool for patient self-evaluation of the severity of a voice disorder.…”
Section: Introductionmentioning
confidence: 98%
“…). Although the mean post‐IL VHI‐10 scores remained within the abnormal range, the mean improvement was clinically meaningful and consistent with the response rates and magnitude of change observed in previous studies . This suggests that IL assists in more efficient phonation and less muscle effort.…”
Section: Discussionmentioning
confidence: 99%